2010
DOI: 10.5152/akd.2010.138
|View full text |Cite
|
Sign up to set email alerts
|

Relation of homocysteine levels with patency and flow rate of infarct related artery in patients receiving fibrinolytic therapy

Abstract: Objective: Elevated homocysteine levels induce a hypercoagulable state and make the clot more resistant to fibrinolysis. In this prospective observational study, we investigated the influence of homocysteine levels on infarct-related artery (IRA) patency and flow as determined with regard to thrombolysis in myocardial infraction (TIMI) flow grade and corrected TIMI frame count (CTFC). Methods: Sixty-one patients who received fibrinolytic therapy for a first ST elevation myocardial infarction (STEMI) within 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Elevated HCY is associated with mortality as well as serious non-fatal outcomes in patients with unstable angina and non-ST-segment elevation myocardial infarction (NSTEMI) [12] , and increased intracoronary thrombus burden in patients with acute coronary syndrome [13–14] . Previous observational studies in patients with STEMI suggested an association between elevated HCY level with impaired STR after fibrinolytic therapy [13,15] . We conducted a retrospective analysis to examine the potential relationship between elevated serum HCY and poor ST-segment resolution (STR) after PPCI.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated HCY is associated with mortality as well as serious non-fatal outcomes in patients with unstable angina and non-ST-segment elevation myocardial infarction (NSTEMI) [12] , and increased intracoronary thrombus burden in patients with acute coronary syndrome [13–14] . Previous observational studies in patients with STEMI suggested an association between elevated HCY level with impaired STR after fibrinolytic therapy [13,15] . We conducted a retrospective analysis to examine the potential relationship between elevated serum HCY and poor ST-segment resolution (STR) after PPCI.…”
Section: Introductionmentioning
confidence: 99%